2021
DOI: 10.3390/ijerph182211797
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Physical Activity, Self-Regulation and Cognitive School Readiness in Preschool Children

Abstract: (1) Background: Limited research exists on the pathways through which physical activity influences cognitive development in the early years. This study examined the direct and indirect relationships between physical activity, self-regulation, and cognitive school readiness in preschool children. (2) Method: Participants (n = 56) aged 3–5 years were recruited from the PLAYCE study, Perth, Western Australia. Physical activity was measured using 7-day accelerometry. Self-regulation was measured using the Head Toe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Our finding of weak positive associations between moderate and vigorous PA intensities and numeracy are consistent with the findings of Bai et al (2021) who found a positive association for both total PA and MVPA with cognitive school readiness (which also included colors, sizes, shape recognition, and comparison ability) in preschoolers. However, other studies in preschoolers have reported no associations between MVPA and numeracy-related outcomes ( Becker et al, 2014 ; St. Laurent et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our finding of weak positive associations between moderate and vigorous PA intensities and numeracy are consistent with the findings of Bai et al (2021) who found a positive association for both total PA and MVPA with cognitive school readiness (which also included colors, sizes, shape recognition, and comparison ability) in preschoolers. However, other studies in preschoolers have reported no associations between MVPA and numeracy-related outcomes ( Becker et al, 2014 ; St. Laurent et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, other studies in preschoolers have reported no associations between MVPA and numeracy-related outcomes ( Becker et al, 2014 ; St. Laurent et al, 2018 ). Yet, since the assessment of outcomes differs with our study and across these studies math achievement by Becker et al (2014) , number recognition by St. Laurent et al (2018) , and school readiness by Bai et al (2021) , the findings may not be directly comparable. Also, Becker et al (2014) only included assessment of PA during outdoor recess sessions, and thus excluded indoor activities and activities after preschool hours.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations